Areal-world evaluation of indacaterol and other bronchodilators in COPD: The INFLOW study - Georges Juvelekian (2018)
© 2015 Juvelekian et al. Aim: INFLOW (INdacaterol eFfectiveness and utiLizatiOn in COPD: real World evaluation) was a prospective, noninterventional study assessing the effectiveness and safety of long-acting bronchodilators in patients with chronic obstructive pulmonary disease (COPD) from the Middle East, Asia, and South Africa. Methods: Patients newly prescribed or switched to indacaterol or other long-acting β2-agonist (LABA), or tiotropium (monotherapy or in combination) were evaluated over 6 months. The primary endpoint was the clinical COPD questionnaire overall score at the end of the study. Results: Data were analyzed from 1,710 patients (mean postbronchodilator forced expiratory volume in 1 second, 59% predicted) who received indacaterol (n=1,179), other LABA (n=68), tiotropium (n=271), indacaterol plus tiotropium (n=167), or other LABA plus tiotropium (n=25). Across treatments, clinical COPD questionnaire overall score improved from baseline by 0.81–1.26 points (all P,0.0001), 63%–84% of patients were satisfied/very satisfied, and physicians rated effectiveness as good/very good in 63%–80% of cases. The indacaterol inhaler was rated easy/very easy to use by the majority of patients, and physicians considered its use clearly understood by most patients. All treatments had acceptable tolerability. Conclusion: In real life clinical practice across a diverse region, indacaterol and other long-acting bronchodilators improved health status and were well regarded by patients and physicians.